Complete removal of textile dyes from aqueous media using ionic-liquid-based aqueous two-phase systems - Ferreira, Ana M.
The textiles manufacturing is one of the core industries which discharges a heavy load of chemicals during the dying process. As a result, the release of large contents of dyes through aqueous effluents leads to both environmental and economic concerns. Aiming at developing more benign methodologies than those studied hitherto, this work proposes a novel approach to remove dyes from aqueous discharges by the use of ionic liquid (IL)-based aqueous two-phase systems (ATPS). A detailed study on the partition coefficients and extraction efficiencies of a set of textile dyes (chloranilic acid, indigo blue and sudan III) using ATPS composed of ILs (phosphonium- and imidazolium-based) and an inorganic (aluminium sulphate) or organic salt (potassium citrate) is here addressed. The gathered data allow the evaluation of the IL chemical structure, the nature of the salt, as well as the pH of the aqueous medium. The results obtained reveal that a proper selection of the IL and salt can lead to the complete extraction of the three dyes to the IL-rich phase in a single-step procedure. Moreover, the dyes recovery to further allow the reuse of the IL-rich phase is also described. This new approach, using hydrophilic ILs, is consequently more environmentally friendly and could be envisaged as a promising process for reducing the pollution of wastewaters. (C) 2014 Elsevier B.V. All rights reserved.